Stranger in paradise - Parker, Robert B., 1932-2010 (A Jesse Stone mystery, 2009)
esse Stone is an ex LA cop who has taken the job of police chief in Paradise, Massachusetts. His drinking and his damaged relationship with his wife, define him as much as his supreme skill at policing his patch. When Crow, an Apache hitman, turns up in Jesse Stone's office, he is intrigued and very much on his guard. Ten years before, Crow was part of a gang that had taken a woman in the town hostage when a bank raid went wrong. The hostages were released unharmed, thanks to Crow's moral view that you didn't kill women, but he also got away with enough money not to have to work again. So why is Crow back in town? Why has he come to see Jesse? And why has he taken a job of kidnapping a young girl and her mother?